Radar attenuation in Europa's ice shell: Obstacles and opportunities for constraining the shell thickness and its thermal structure. Issue 3 (20th March 2017) - Kalousová, Klára; Schroeder, Dustin M.; Soderlund, Krista M.
Abstract: Young surface and possible recent endogenic activity make Europa one of the most exciting solar system bodies and a primary target for spacecraft exploration. Future Europa missions are expected to carry ice‐penetrating radar instruments designed to investigate its subsurface thermophysical structure. Several authors have addressed the radar sounders' performance at icy moons, often ignoring the complex structure of a realistic ice shell. Here we explore the variation in two‐way radar attenuation for a variety of potential thermal structures of Europa's shell (determined by reference viscosity, activation energy, tidal heating, surface temperature, and shell thickness) as well as for low and high loss temperature‐dependent attenuation model. We found that (i) for all investigated ice shell thicknesses (5–30 km), the radar sounder will penetrate between 15% and 100% of the total thickness, (ii) the maximum penetration depth varies laterally, with deepest penetration possible through cold downwellings, (iii) direct ocean detection might be possible for shells of up to 15 km thick if the signal travels through cold downwelling ice or the shell is conductive, (iv) even if the ice/ocean interface is not directly detected, penetration through most of the shell could constrain the deep shell structure through returns from deep non‐ocean interfaces or the loss of signal itself, and (v) for all plausible ice shells, the two‐way attenuation to the eutectic point is ≲ 30 dB which shows a robust potential for longitudinal investigation of the ice shell's shallow thermophysical structure. Key Points: We explore radar attenuation for a variety of potential thermal structures of Europa's shell and two end‐member attenuation models We show that the deepest signal penetration is possible through cold downwellings with direct ocean detection for shells of up to 15 km Our results support the possibility to detect the eutectic isotherm for all plausible shell thicknesses